2022
DOI: 10.3390/antiox11010123
|View full text |Cite
|
Sign up to set email alerts
|

Meso-Dihydroguaiaretic Acid Ameliorates Acute Respiratory Distress Syndrome through Inhibiting Neutrophilic Inflammation and Scavenging Free Radical

Abstract: The pathogenesis of acute respiratory distress syndrome (ARDS) is very complex. Patients with ARDS still suffer high mortality rates. Infiltration and activation of neutrophils in lungs are critical pathogenic factors in ARDS. In this study, we demonstrate that meso-dihydroguaiaretic acid (MDGA), a natural lignan, inhibits inflammatory responses in human neutrophils and ameliorates ARDS in mice. MDGA inhibited superoxide anion generation and elastase release in various G-protein coupled receptor agonists-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Meso-dihydroguaiaretic acid demonstrated strong free radical scavenging activity in various cell-free assays, modulated MAPKs/Akt signal pathways in G-protein coupled receptor agonists-induced human neutrophils, and reduced ROS generation. In a murine model of LPS-induced acute respiratory distress syndrome, the lignan application showed anti-neutrophilic inflammatory effects [ 58 ].…”
Section: Lignans With Antioxidant and Anti-inflammatory Actionmentioning
confidence: 99%
“…Meso-dihydroguaiaretic acid demonstrated strong free radical scavenging activity in various cell-free assays, modulated MAPKs/Akt signal pathways in G-protein coupled receptor agonists-induced human neutrophils, and reduced ROS generation. In a murine model of LPS-induced acute respiratory distress syndrome, the lignan application showed anti-neutrophilic inflammatory effects [ 58 ].…”
Section: Lignans With Antioxidant and Anti-inflammatory Actionmentioning
confidence: 99%
“…Our data showed that IA‐1 attenuated elastase release in LPS‐induced inflamed lung tissue and in activated human neutrophils. Oxidative stress induced by excess ROS generation leads to proinflammatory cytokine production and lung tissue damage in ARDS (Lee et al, 2022). In our study, LPS‐induced oxidative stress was diminished in IA‐1‐pretreated mice compared to sham‐treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…Free radicals break down cells and tissues, affecting metabolic function and causing varying degrees of health problems. For example, common cancers [1], aging [2], diabetes [3], respiratory diseases [4], nervous system diseases [5], and so on are all related to oxidative free radicals. If excessive oxidative free radicals are eliminated, many aging and related diseases caused by free radicals can be prevented.…”
Section: Introductionmentioning
confidence: 99%